Building capacity in risk-benefit assessment of foods: Lessons learned from the RB4EU project - Assuncao, R (2019)
Background: Human diet may present both risks and benefits to consumers' health. Risk-benefit assessment of foods (RBA) intends to estimate the overall health impact associated with exposure (or lack of exposure) to a particular food or food component. Scope and approach: "RiskBenefit4EU - Partnering to strengthen the risk-benefit assessment within EU using a holistic approach" (RB4EU) is a project funded by the European Food Safety Authority (EFSA) that integrates a multidisciplinary team from Portugal, Denmark and France. This project aims to strengthen the EU capacity to assess and integrate food risks and benefits regarding toxicology, microbiology and nutrition. One of the specific objectives of RB4EU was to build capacity in RBA among the recipient partners from Portugal. In order to achieve this objective, a capacity building strategy including theoretical and hands-on training and the development of a case-study were established. This paper aims to present the strategy used in the RB4EU project to build capacity within RBA, including the main training approaches and the lessons learned. Key findings and conclusions: The capacity-building program included three main activities: theoretical training, focusing on RBA concepts; hands-on training, applying the acquired concepts to a concrete case-study, using the methods and tools displayed; and scientific missions, intending to provide advanced training in specific domains of RBA. The developed strategy can be used in the future to build capacity within RBA.